2004
DOI: 10.1111/j.1540-8159.2004.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Quinidine in Treatment of Electrical Storm in Brugada Syndrome

Abstract: We report an adolescent with a malignant form of Brugada syndrome who presented with 15 episodes of ventricular fibrillation (VF) over 10 days, shortly after implantation of an implantable cardioverter defibrillator. Oral quinidine bisulphate at a dose of 1000 mg/day successfully suppressed the electrical storm and recurrence of VF over 18-month follow-up. It also normalized the ST-segment elevation in his right precordial leads, suppressed all ambient unifocal ventricular extrasystoles and induction of VF on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 6 publications
7
43
0
Order By: Relevance
“…13 The effectiveness of quinidine in treating ES in patients with BS has been indicated in some reports. 2,3 Cilostazol, an oral phosphodiesterase type III inhibitor that increases ICa, is also reported to have suppressed the frequently occurring VF episodes in a patient with BS 4 In the present case, ISP successfully normalized the STsegment and suppressed the occurrence of VF. However, quinidine and cilostazol were ineffective in suppressing VF.…”
Section: Discussionmentioning
confidence: 64%
“…13 The effectiveness of quinidine in treating ES in patients with BS has been indicated in some reports. 2,3 Cilostazol, an oral phosphodiesterase type III inhibitor that increases ICa, is also reported to have suppressed the frequently occurring VF episodes in a patient with BS 4 In the present case, ISP successfully normalized the STsegment and suppressed the occurrence of VF. However, quinidine and cilostazol were ineffective in suppressing VF.…”
Section: Discussionmentioning
confidence: 64%
“…It is of utmost importance to try and understand the substrate of incessant arrhythmias, because if a diagnosis is established, a targeted treatment may be possible. For example, in Brugada syndrome, quinidine or isoproterenol may terminate incessant arrhythmias (139,395). In acute ischemia, intravenous amiodarone seems more effective than other antiarrhythmic drugs (396).…”
Section: Managementmentioning
confidence: 99%
“…The authors concluded that quinidine effectively suppresses VF induction as well as spontaneous arrhythmias in patients with Brugada syndrome and may be useful as an adjunct to ICD therapy or as an alternative to ICD in cases in which an ICD is refused, unaffordable, or not feasible for any reason. These results are consistent with those reported the same group in prior years (Belhassen et al 1999(Belhassen et al 2002 and more recently by other investigators (Hermida et al 2004;Mok et al 2004). The data highlight the need for randomized clinical trials to assess the effectiveness of quinidine, preferably in patients with frequent events who have already received an ICD.…”
Section: Pharmacologic Approach To Therapysupporting
confidence: 82%
“…Isoproterenol, sometimes in combination with quinidine, has been shown to be effective in normalizing ST segment elevation in patients with the Brugada syndrome and in controling electrical storms, particularly in children (Alings et al 2001;Shimizu et al 2000b;Suzuki et al 2000;Tanaka et al 2001;Belhassen et al 2002;Mok et al 2004).…”
Section: Pharmacologic Approach To Therapymentioning
confidence: 99%
See 1 more Smart Citation